ENHANCING GRAMMAR LEARNING: IMPLEMENTING KAHOOT AS AN EVALUATION TOOL IN INDONESIAN HIGH SCHOOLS - Siti Khadijah Barus; Maryati Salmiah (Indonesian EFL Journal, 2024)
This study explores the implementation of Kahoot as an evaluation tool to enhance grammar learning, identify its benefits and challenges, and assess student responses. Using a qualitative case study design, data were collected through classroom observations, interviews, and questionnaires involving an English teacher and 27 high school students in Medan. Thematic analysis revealed that Kahoot effectively improves grammar understanding, increases student motivation and interaction, and is user-friendly. Despite some technical challenges, the majority of students responded positively. The study recommends broader adoption of Kahoot in educational settings to enrich the learning experience.Keywords: Evaluation; implementation; Kahoot; teaching English grammar.